Cadre Training in Detecting Toddler Development in Ketimang Village, Wonoayu District: Pelatihanan Kader Dalam Deteksi Perkembangan Anak Balita Di Desa Ketimang Kecamatan Wonoayu - Cholifah, Siti; Purwanti, Yanik Purwanti; Rohmah, Jamilatur; Aini, Latifatul (Procedia of Social Sciences and Humanities, 2022)
A child has the characteristics of growing and developing. Children's growth can be seen from the increase in weight and height, while development can be monitored from fine motor skills, gross motor skills, speech and language skills, socialization and independence of children. Early detection of development is very important so that babies and toddlers who experience delays can immediately get treatment and stimulation. The purpose of community service activities is to increase the knowledge and skills of cadres to detect the development of infants and toddlers. Based on the results of surveys and interviews in Ketimang village, routine posyandu activities are weighed for monitoring child growth, but this has not been accompanied by development monitoring by cadres, due to lack of knowledge of cadres about detecting child development, besides the duties and activities of village midwives are very tight so there is no opportunity. to train cadres and carry out routine development detection at posyandu. The solution offered is to conduct cadre training to detect child development according to the agreement carried out on February 12, 2022 at the home of the posyandu cadre head. The implementation method starts with conducting surveys, preparing the Developmental Pre-Screening Questionnaire (KPSP) media, and implementing training and evaluating activities. The results of the activity, this community service was attended by 17 posyandu cadres, before training 10 cadres (58.9%) had less knowledge about developmental detection, after training they became well-informed and 7 cadres (41.1%) had good knowledge after training they became well-informed. very good knowledge. This shows that there is an increase in the knowledge and skills of cadres in detecting the development of infants under five.